2009
DOI: 10.1086/599122
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte‐Derived Dendritic Cells from HIV Type 1–Infected Individuals Show Reduced Ability to Stimulate T Cells and Have Altered Production of Interleukin (IL)–12 and IL‐10

Abstract: Monocyte-derived dendritic cells (MDDCs) have been used in therapeutic vaccination for cancer. A small number of studies have employed a similar approach to vaccinate human immunodeficiency virus (HIV)-infected individuals. We have thus analyzed the functional properties of MDDCs generated from HIV-infected individuals who either are receiving highly active antiretroviral therapy or are therapy naive. There was no difference in the MDDC phenotype or efficiency of MDDC generation between HIV-infected individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 36 publications
5
34
1
5
Order By: Relevance
“…The high affinity IL-23 receptor complex is comprised of an IL-12R 1 (as found in IL-12 receptor) and a unique IL-23R subunit (Parham, Chirica et al, 2002). As mentioned in the previous section on IL-12, many studies have shown the effect of HIV infection on the production of IL-12 and IL-12 receptor expression; there is strong evidence suggesting that IL-12 production is impaired in cells infected in vitro with HIV and in HIV positive patients (Chehimi, Starr et al, 1994;Marshall, Chehimiet al, 1999;Daftarian, Diaz-Mitoma et al, 1995;Boucher, Parato et al, 2010;Buisson, Benlahrech et al, 2009). Since IL-12 and IL-23 share the p40 subunit as well as the IL-12R1 receptor subunit, it is interesting to speculate on the impact of HIV on IL-23 function and the involvement of IL-23 in HIV pathogenesis.…”
Section: Il-23 and Hiv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high affinity IL-23 receptor complex is comprised of an IL-12R 1 (as found in IL-12 receptor) and a unique IL-23R subunit (Parham, Chirica et al, 2002). As mentioned in the previous section on IL-12, many studies have shown the effect of HIV infection on the production of IL-12 and IL-12 receptor expression; there is strong evidence suggesting that IL-12 production is impaired in cells infected in vitro with HIV and in HIV positive patients (Chehimi, Starr et al, 1994;Marshall, Chehimiet al, 1999;Daftarian, Diaz-Mitoma et al, 1995;Boucher, Parato et al, 2010;Buisson, Benlahrech et al, 2009). Since IL-12 and IL-23 share the p40 subunit as well as the IL-12R1 receptor subunit, it is interesting to speculate on the impact of HIV on IL-23 function and the involvement of IL-23 in HIV pathogenesis.…”
Section: Il-23 and Hiv Infectionmentioning
confidence: 99%
“…IL-12 expression drives the production and development of the Th1 subset of T cells, and is responsible for the induction of IFN- expression from these cells(Alber, Al-Robaiy et al, 2006). IL-12 production is impaired in HIV-infected individuals and in cells infected in vitro with HIV (Chehimi, Starr et al, 1999;Daftarian, Diaz-Mitoma et al, 1995;Boucher, Parato et al, 2010;Buisson, Benlahrech et al, 2009). In terms of IL-12 receptor chain expression (IL-12R1 and IL-12R2), one study reported that resting peripheral blood mononuclear cells (PBMC) from HIV positive patients and HIV negative controls did not express IL-12R 1 or IL-12R 2 chains on their cell surface (Jones, Young et al, 2003).…”
Section: Il-12 and Hiv Infectionmentioning
confidence: 99%
“…IL-12 production was shown to be impaired in the course of infection, and the relevance of its deficiency in virusinduced pathogenesis is suggested by the finding that exogenous administration of this cytokine restores immune responsiveness of peripheral leukocytes from AIDS patients (36). Furthermore, monocyte-derived DC generated from HIV-infected individuals exhibit an unbalanced IL-12/IL-10 ratio and have a reduced capacity to stimulate IFN-␥ secretion in both T lymphocytes (37) and natural killer cells (38). In this regard, it has been reported that IL-12, in addition to exerting a proliferative and Th1-polarizing effect on conventional ␣␤ T lymphocytes, is also critical for the activation and proliferation of ␥␦ T cells (39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Diminished levels and dysfunctional dendritic cells (DCs) are also frequently observed and may contribute to an overall impairment of adaptive immunity (6)(7)(8).…”
Section: Aids Progression Is Characterized By Depletion and Functionamentioning
confidence: 99%
“…The use of DCs as a vehicle for vaccines against tumors and infectious agents is being investigated by several research groups and seems to be well tolerated in vivo (25)(26)(27). DC-based vaccines are particularly promising in the context of HIV infection, in which alterations in the number and function of DCs seems to correlate with disease progression (6)(7)(8). Indeed, there is emerging evidence that antigen-pulsed DCs offers better control of plasma viremia in HIV-1-infected individuals.…”
Section: Aids Progression Is Characterized By Depletion and Functionamentioning
confidence: 99%